2015
DOI: 10.1186/s13063-014-0525-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective or stepwise removal of deep caries in deciduous molars: study protocol for a randomized controlled trial

Abstract: BackgroundFor treating deep caries lesions, selective or stepwise (one- and two-step) incomplete excavation seems advantageous compared with complete caries removal. However, current evidence regarding the success, as defined by not requiring any retreatments, or survival of teeth after different excavations is insufficient for definitive recommendation, especially when treating deciduous teeth. Moreover, restoration integrity has not been comparatively analyzed longitudinally, and neither patients’, dentists’… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
16
0
3
Order By: Relevance
“…Modified Ryge criteria from USPHS guidelines had been used to evaluate the restorations in this study. These criteria had been used in the majority of clinical research before and reliable criteria to be used in evaluating restorations [15,16,17]. However, the criteria did not have any radiograph examination.…”
Section: Discussionmentioning
confidence: 99%
“…Modified Ryge criteria from USPHS guidelines had been used to evaluate the restorations in this study. These criteria had been used in the majority of clinical research before and reliable criteria to be used in evaluating restorations [15,16,17]. However, the criteria did not have any radiograph examination.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, as this is a recent technique, its disadvantage is that it requires more longitudinal studies, even though it already shows positive results in research performed with permanent and primary teeth. 12, [36][37][38][39][40]…”
Section: • Selective Removal Of Carious Tissuementioning
confidence: 99%
“…Thus, for treating deep carious lesions, selective or gradual removal of decayed tissue, done in one and two clinical sessions respectively, seems to have an advantage over the total removal of decayed tissue 44 . However, since several studies have found residual lesions arrested using clinical and microbiological criteria, after adequate sealing of the cavity, the need for the reopening of the tooth has been increasingly questioned 20 .…”
Section: Sealing Carious Lesionsmentioning
confidence: 99%